Analisis Statistik Frekuensi Kejadian Gempabumi Menurut Sistem Kalender Qomariyah - Hardiyanto, Sebastian; Rizky Muhammad Rahman, (JFT: Jurnal Fisika dan Terapannya, 2024)
Indonesia is in three active tectonic plates junction which causes tectonic activity in Indonesia to be high. The statistical method is often to be used by researchers in examining the relationship of earthquake’s frequencies with the other related parameters. In this study, the author tries to link the frequency of earthquakes that occurred in the Hijriy calendar system for the aim of finding a correlation between Islamic literature and earthquake natural disasters. Gregorian calendar is basically different from Hijriy calendar system. For this reason, various parameters of almanac and astronomy such as Julian Day, Sun Declination, Hour Angle and etc are calculated to determine the deadline of changing days on the Hijriy calender (Maghrib time) for correcting origin time from Gregorian to Hijriy calendar. The data used in this study was earthquake data for Indonesian region which is located between 6º N - 11º S and 95º - 141º E. Data was taken from the USGS site from January 1900 to October 2019 with magnitude ≥ 5 Richter. The results of these mathematical calculations concluded that the smallest earthquake’s frequency occurred on al-Jumu'ah (Friday) during the period of 1900 - 2019.